2021
DOI: 10.1108/ijrdm-11-2020-0475
|View full text |Cite
|
Sign up to set email alerts
|

E-tailers adaptation during early stages of “social distancing causing crises”: an exploratory study

Abstract: PurposeThis paper studies the impact of social distancing causing crises (SDCC) such as pandemics in its early stages on e-tailers demand and supply side operations and provides a conceptual framework for adaptation.Design/methodology/approachA grounded theory-based approach has been used, wherein journal papers and news articles are the key data sources. Standard qualitative methodology, including open, axial and selective coding has been followed.FindingsThe study provides second order themes derived from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…The study among other things concluded that women have long-term orientation towards the sustainability of family business and can overcome conflicts through adaptive mechanisms. Adapting to online platforms as a mechanism to enhance sales volumes thus becomes inevitable [10]. We hypothesise the following based on the extant literature on the connection between online sales and resilience during pandemic:…”
Section: Online Sale and Financial Resilience During Pandemicmentioning
confidence: 99%
“…The study among other things concluded that women have long-term orientation towards the sustainability of family business and can overcome conflicts through adaptive mechanisms. Adapting to online platforms as a mechanism to enhance sales volumes thus becomes inevitable [10]. We hypothesise the following based on the extant literature on the connection between online sales and resilience during pandemic:…”
Section: Online Sale and Financial Resilience During Pandemicmentioning
confidence: 99%
“…The retail landscape is transforming in light of the pandemic, as well as through digitalization and prevalence of omni-channel approaches to distribution (Frasquet et al, 2021;Verhoef et al, 2015;Halan, 2021). These shifts entail complexities in pricing, services, human resources, know-how, as well as last mile (LM) logistics practices (H€ ubner et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Such a dynamic environment not only affects business strategies but also raises the need for innovative logistics practices and flexibility (Cao, 2014;Jeanpert and Pach e, 2016;Jocevski et al, 2019;Lim and Winkenbach, 2018;Sandberg, 2021), notably because firm characteristics evolve over time (Davis-Sramek et al, 2020). For instance, during the COVID-19 pandemic, increased consumer demand for contactless shopping (Halan, 2021) and home deliveries (HD) has prompted retailers and LSPs to explore autonomous delivery robots (Pani et al, 2020). Given the inconsistencies among firms, there does not exist one magic LM practice fitting all retailers, given its importance in differentiation and positioning (Ishfaq et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magableh (2021:13) debate that the COVID-19 pandemic is different from other 'Black Swan' events as it simultaneously disrupted both demand and supply. Supply disruptions originated from delays in delivering certain raw materials and imports, whilst demand was disrupted because of the sudden changes in consumer lifestyles, which wholly altered consumers' way of living, working and shopping (Halan 2021). Indeed, traditional SCD planning, mitigation, and recovery strategies were insufficient in responding to the mega disruptions caused by the COVID-19 pandemic (Paul & Chowdhury 2020:284).…”
Section: Introductionmentioning
confidence: 99%